Legislating Racism : The Billion Dollar Congress and the Birth of Jim Crow - Upchurch, Thomas Adams (Book collections on Project MUSE., 2004)
The Civil War and Reconstruction were characterized by two lasting legacies -- the failure to bring racial harmony to the South and the failure to foster reconciliation between the North and South. The nation was left with a festering race problem, as a white-dominated society and political structure debated the +proper role for blacks. At the national level, both sides harbored bitter feelings toward the other, which often resulted in clashes among congressmen that inflamed, rather than solved, the race problem. No Congress expended more energy debating this issue than the Fifty-First.